Improving productivity through the implementation of lean manufacturing and SLP Tools in a footwear SME - Pérez Vivanco, Eriksson Wagner (2025)
In Peru, a lack of technological investments and training contributes to low productivity in the footwear industry. The study presents a comprehensive project to improve the productivity of a Micro and Small Enterprise (MSE) in Peru's footwear industry, using Lean Manufacturing tools. The methodology includes TPM for inefficient material distribution, 5S for policy procedures and underutilized spaces, and SLP for disorder in work areas. Pilot tests of 5S demonstrate significant improvements, and the implementation of TPM aims to avoid accidents and enhance equipment efficiency. The resulting 80% increase in overall company productivity is supported by positive economic evaluations, including a Net Present Value (NPV) of 26,858.27 PEN, an Internal Rate of Return (IRR) of 62%, a Payback Period (PRI) of 2.39 years, and a Benefit-Cost Ratio (B/C) of 2.27. Overall, this integrated approach proves successful in elevating the company's overall efficiency.